2011
DOI: 10.1302/0301-620x.93b10.27100
|View full text |Cite
|
Sign up to set email alerts
|

Age at hip or knee joint replacement surgery predicts likelihood of revision surgery

Abstract: We compared revision and mortality rates of 4668 patients undergoing primary total hip and knee replacement between 1989 and 2007 at a University Hospital in New Zealand. The mean age at the time of surgery was 69 years (16 to 100). A total of 1175 patients (25%) had died at follow-up at a mean of ten years post-operatively. The mean age of those who died within ten years of surgery was 74.4 years (29 to 97) at time of surgery. No change in comorbidity score or age of the patients receiving joint replacement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 10 publications
3
42
2
1
Order By: Relevance
“…Furthermore, because the volume of TKAs is disproportionately increasing in younger patients, function and satisfaction in this group of patients becomes even more important [23,43]. In a retrospective review of 60 patients with a mean age of 55.4 years by Price et al [35], 25 (42%) reported persistent pain, and implant survivorship was only 82% at 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the volume of TKAs is disproportionately increasing in younger patients, function and satisfaction in this group of patients becomes even more important [23,43]. In a retrospective review of 60 patients with a mean age of 55.4 years by Price et al [35], 25 (42%) reported persistent pain, and implant survivorship was only 82% at 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Current joint registries record between 92% at 11 years and 86% at 22 years survival for these implants [14,15,18] . These improved survival statistics have been interpreted as a cemented THR is likely to be a "life long" implant for patients aged sixty-two or older, whereas for a fifty-eight-year-old patient there is a 50:50 chance of undergoing a revision within their life time [23] . There are currently two philosophies of cemented femoral fixation: composite beam and polished, tapered wedge.…”
Section: Modern Primary Femoral Stemmentioning
confidence: 99%
“…While originally considered a procedure for older, less active patients, in the past decade, younger and presumably more active patients have been the fastest growing segment of the TKA population [35]. TKA in young patients has been associated with higher rates of revision [63] and residual symptoms and dissatisfaction [50]. Surgical techniques and component designs have evolved in recent years that have focused on improving function and outcome after TKA.…”
Section: Introductionmentioning
confidence: 99%